Implementasi Kurikulum Merdeka dalam Mengatasi Krisis Pembelajaran (Loss Learning) Akibat Pandemi di Sekolah - Juliana Margareta Sumilat; Fitriah Mochtar (Journal on Education, 2024)
The pandemic in Indonesia has an impact on life, especially education. This research aims to explain the independent curriculum as an attempt to address the learning loss post pandemic that is occurring in Indonesia. This article is intended to provide information and an overview of any aspect offered by an independent curriculum about how the planning, implementation and evaluation of the curricula itself is independent, as far as providing solutions in the world of education to cope with the learning crisis that occurs after pandemic. This article used the method of Library Research. Library research is gathering data information from a variety of sources, such as books, articles, and journals, relevant to the research topic of Indarta et al. (2022). In this case, researchers gather library data, information that has been previously documented in the form of books, magazines, and articles. The output of this study show that a new curriculum has been created, namely that the Government's Free Curriculum is able to deal with the phenomenon of learning loss that occurs after a pandemic among pupils.